Exclusive breastfeeding after breast cancer. Case study - Poupas Martins, Maria Antónia; Sim-Sim, Margarida (Investigación y Educación en Enfermería, 2023)
Objective. To develop a care plan focused on assisting a puerperal woman who decides to feed their child through breastfeeding on the contralateral breast. Methods. A case study conducted with a 36-year-old primiparous woman who underwent tumorectomy and left axillary emptying, chemotherapy and radiotherapy 8 years ago. The data were collected in the Nursing process, with initial assessment using the Marjory Gordon functional health patterns. The care plan used the NANDA-I, NIC and NOC taxonomies. Results. Three diagnoses were identified: [00208] Readiness for Enhanced Childbearing Process, [00106] Readiness for Enhanced Breastfeeding and [00167] Readiness for Enhanced Self-Concept. The indicators were evaluated in the initial and later phase, with gains in the first two diagnoses. The third diagnosis proved to be partially sufficient, as it did not allow assessing the developmental and non-pathological self-image in the puerperium. In the puerperal phase, maternal roles are challenging and demanding. Nursing care contributed to the adaptation to breastfeeding in the contralateral breast and to the guarantee of adequate nutrition for the newborn. The childbearing process was strengthened. Breastfeeding is carried out with maternal satisfaction, good latch and normal weight evolution in the newborn. Conclusion. The case study strengthened knowledge by addressing a little investigated theme. The NANDA-I taxonomy may need further study in the Self-perception domain, more specifically in the self-image reported during the pregnancy-puerperal phase.